Expression of huntingtin-associated protein 1 in adult mouse dorsal root ganglia and its neurochemical characterization in reference to sensory neuron subpopulations. (December 2020) - Islam, Md Nabiul; Maeda, Naoki; Miyasato, Emi; Jahan, Mir Rubayet; Tarif, Abu Md Mamun; Ishino, Taiga; Nozaki, Kanako; Masumoto, Koh-hei; Yanai, Akie; Shinoda, Koh
Highlights: This study is the first to examine HAP1-expression in dorsal root ganglia (DRG). HAP1 is highly co-expressed with the markers of nociceptive/proprioceptive neurons. HAP1 is completely lacking in the touch-sensitive DRG neurons. HAP1 may play an important role in modulating nociceptive/proprioceptive functions. It will be of great interest to clarify the pathophysiological role of HAP1 in DRG. Abstract: Huntingtin-associated protein 1 (HAP1) is a polyglutamine (polyQ) length-dependent interactor with causal agents in several neurodegenerative diseases and has been regarded as a protective factor against neurodegeneration. In normal rodent brain and spinal cord, HAP1 is abundantly expressed in the areas that are spared from neurodegeneration while those areas with little HAP1 are frequent targets of neurodegeneration. We have recently showed that HAP1 is highly expressed in the spinal dorsal horn and may participate in modification/protection of certain sensory functions. Neurons in the dorsal root ganglia (DRG) transmits sensory stimuli from periphery to spinal cord/brain stem. Nevertheless, to date HAP1 expression in DRG remains unreported. In this study, the expression of HAP1 in cervical, thoracic, lumbar and sacral DRG in adult male mice and its relationships with different chemical markers for sensory neurons were examined using Western blot and immunohistochemistry. HAP1-immunoreactivity was detected in the cytoplasm of DRG neurons, and the percentage of HAP1-immunoreactive (ir) DRG neurons was ranged between 28–31 %. HAP1-immunoreactivity was comparatively more in the small cells (47–58 %) and medium cells (40–44 %) than that in the large cells (9–11 %). Double-immunostaining for HAP1 and markers for nociceptive or mechanoreceptive neurons showed that about 70–80 % of CGRP-, SP-, CB-, NOS-, TRPV1-, CR- and PV-ir neurons expressed HAP1. In contrast, HAP1 was completely lacking in TH-ir neurons. Our current study is the first to clarify that HAP1 is highly expressed in nociceptive/proprioceptive neurons but absent in light-touch-sensitive TH neurons, suggesting the potential importance of HAP1 in pain transduction and proprioception.